2009
DOI: 10.1002/pmic.200800473
|View full text |Cite
|
Sign up to set email alerts
|

Improving sensitivity in proteome studies by analysis of false discovery rates for multiple search engines

Abstract: LC-MS experiments can generate large quantities of data, for which a variety of database search engines are available to make peptide and protein identifications. Decoy databases are becoming widely used to place statistical confidence in result sets, allowing the false discovery rate (FDR) to be estimated. Different search engines produce different identification sets so employing more than one search engine could result in an increased number of peptides (and proteins) being identified, if an appropriate mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 20 publications
0
125
0
Order By: Relevance
“…Searches were performed using ProteinPilot (Shilov et al 2007) [version 3.0, settings: Search-Rapid; Instrument-OrbiFT MS (1-3 ppm), LTQ MS/MS; Enzyme-Trypsin; FDR Analysis-Yes] against the target database concatenated to its decoy database counterpart (Tang et al 2008). False discovery rates (FDRs) were calculated as described (Kall et al 2008;Jones et al 2009;Bitton et al 2010) (Table S7). Only peptides with confidence levels .95% were considered.…”
Section: Fission Yeast Techniquesmentioning
confidence: 99%
“…Searches were performed using ProteinPilot (Shilov et al 2007) [version 3.0, settings: Search-Rapid; Instrument-OrbiFT MS (1-3 ppm), LTQ MS/MS; Enzyme-Trypsin; FDR Analysis-Yes] against the target database concatenated to its decoy database counterpart (Tang et al 2008). False discovery rates (FDRs) were calculated as described (Kall et al 2008;Jones et al 2009;Bitton et al 2010) (Table S7). Only peptides with confidence levels .95% were considered.…”
Section: Fission Yeast Techniquesmentioning
confidence: 99%
“…We analyzed the number of FDR filtered PSMs for each single search engine and their combinations before performing any protein inference evaluation. The benefit of combining search engine results for spectrum identification has already been shown extensively in other publications (44,45). It is generally accepted that search engines in combination yield more valid PSMs, especially in low-resolution fragment ion measurements (see section 1 in the Supplemental Files S3-S11).…”
Section: General Assessment Of the Protein Inference Algorithmsmentioning
confidence: 81%
“…1). It is reported that peptides identified by two or more pipelines have fewer errors than the ones identified by only one pipeline (34,36). In fact, when we consider only the high confidence novel peptides (identified by two or more pipelines), performances of ITP, PA, and Enosi are similar.…”
Section: Proteogenomic Findings Expand the Microglial Proteomicmentioning
confidence: 92%
“…1). The combination of multiple search engines and result integration increases both sensitivity and specificity in peptide discovery (33,34) and should be a beneficial practice in proteogenomics. It is developed upon the core of our previous automated prokaryotic analysis framework, GenoSuite, where four peptide identification algorithms, OMSSA (30), X!Tandem (31), InsPecT (35), and MassWiz (36) were configured for peptide identification.…”
Section: Methodsmentioning
confidence: 99%